2023
DOI: 10.1109/access.2023.3281652
|View full text |Cite
|
Sign up to set email alerts
|

A Density Peaking Clustering Algorithm for Differential Privacy Preservation

Hua Chen,
Kehui Mei,
Yuan Zhou
et al.

Abstract: The privacy protection problem in data mining has received increasingly attention and is a hot topic of current research. To address the problems of large accuracy loss and instability of clustering results of clustering algorithms under differential privacy protection requirements, a density peak clustering algorithm for differential privacy protection (DP-chDPC) is proposed. Firstly, the original DPC algorithm is improved, by using the dichotomy method to automatically determine the truncation distance to av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…From the experiments performed and the results obtained (Tables 3 and 4 ), it is revealed that the ARI obtained on the given data sets is better than other approaches [ 15 , 18 , 28 , 29 , 30 ]. The other observed phenomenon is that whenever clustering is performed using the SOM, the most optimum 2D configuration would be preferable by considering the ST or CH score to obtain optimized results because the WM of the SOM is also very meaningful.…”
Section: Conclusion and Future Scopementioning
confidence: 93%
“…From the experiments performed and the results obtained (Tables 3 and 4 ), it is revealed that the ARI obtained on the given data sets is better than other approaches [ 15 , 18 , 28 , 29 , 30 ]. The other observed phenomenon is that whenever clustering is performed using the SOM, the most optimum 2D configuration would be preferable by considering the ST or CH score to obtain optimized results because the WM of the SOM is also very meaningful.…”
Section: Conclusion and Future Scopementioning
confidence: 93%
“…To address concerns regarding the LDA model and the potential exposure of textual information in the training process, Zhao et al 16 proposed several differential privacy LDA algorithms tailored to typical training scenarios. Chen et al 17 introduces a differential privacy‐preserving density peak clustering algorithm to address privacy protection concerns in data mining. Han et al 18 proposes a cluster‐based hierarchical federated learning framework with both differential privacy and secure aggregation.…”
Section: Related Workmentioning
confidence: 99%
“…Using the dichotomy method [30] to determine the cutoff distance d c can solve the subjectivity of the traditional method by setting the truncation percentage p, the main process is as follows:…”
Section: Determination Of Cutoff Distance By Dichntomymentioning
confidence: 99%
“…Based on the literature [29,30], this paper proposes the use of cosine distance instead of Euclidean distance to measure the similarity of high-dimensional datasets, and the use of dichotomy to determine truncation distance adaptively. Aiming at the subjective selection of clustering centers, from the perspective of the decision graph, this paper establishes the constraint conditions of the decision graph statistics by Chebyshev inequality, and then the threshold of statistics ρ and δ are obtained, and the selection of clustering centers is achieved by adjusting the constraint parameters, the improved DPC algorithm based on Chebyshev inequality (CDPC) is proposed.…”
Section: An Improved Dpc Algorithm Based On Chebyshev Inequality and ...mentioning
confidence: 99%
See 1 more Smart Citation